2009
DOI: 10.1089/ten.tea.2008.0362
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Synthetic Dermis and Skin Based on a Self-Assembled Peptide Hydrogel Scaffold

Abstract: Using biocompatible peptide hydrogel as a scaffold, we prepared three-dimensional synthetic skin that does not contain animal-derived materials or pathogens. The present study investigated preparation methods, proliferation, and functional expression of fibroblasts in the synthetic dermis and differentiation of keratinocytes in the epidermis. Synthetic dermis was prepared by mixing fibroblasts with peptide hydrogel, and synthetic skin was prepared by forming an epidermal layer using keratinocytes on the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…A wide range of techniques such as electrospinning, spray deposition, selfassembly, polyelectrolyte multilayer methodologies, and a decellularized ECM have been used to fabricate structures that mimic BM based on natural and synthetic polymers. [25][26][27][28][29] In each organ, a tissue-specific ECM regulates the functionality of epithelial cells. These epithelial cell/ECM interactions need to be replicated for the regeneration of the tissue.…”
Section: Functional Epithelium For Regenerative Medicinementioning
confidence: 99%
“…A wide range of techniques such as electrospinning, spray deposition, selfassembly, polyelectrolyte multilayer methodologies, and a decellularized ECM have been used to fabricate structures that mimic BM based on natural and synthetic polymers. [25][26][27][28][29] In each organ, a tissue-specific ECM regulates the functionality of epithelial cells. These epithelial cell/ECM interactions need to be replicated for the regeneration of the tissue.…”
Section: Functional Epithelium For Regenerative Medicinementioning
confidence: 99%
“…support of a wide range of biological applications, including osteoblast proliferation and differentiation, [26,27] axon regeneration, [28] and keratinocyte differentiation. [29] In addition to applications in tissue regeneration, RAD16-I was recently investigated as a 3D model for ovarian cancer cells, and was found to promote 3D cell adhesion and migration. [30] It was found that ovarian cancer cells on the matrix exhibited a higher resistance to anticancer drugs compared to cells grown on a 2D culture plate, allowing for improved anticancer drug screening and in vitro investigation of tumor biology.…”
Section: β-Sheet Forming Peptide Hydrogelsmentioning
confidence: 99%
“…[156] Self-assembled peptide nanofibers have also been used to create hydrogels with controlled presentations of RGD and other cell adhesion ligands. [134] Such materials have been used to study bone regeneration therapies[164], culturing of synthetic dermis[165], and tubulogenesis of endothelial cells[166], among other biomedical applications[167]. …”
Section: Investigating Cell Behaviors In 3dmentioning
confidence: 99%